Accelerated differentiation of human induced pluripotent stem cells into regionally specific dorsal and ventral spinal neural progenitor cells for application in spinal cord therapeutics - Huntemer-Silveira, Anne; Malone, Dane; Frie, Anna; Walsh, Patrick; Parr, Ann M. (Frontiers in Neuroscience, 2023)
Spinal cord injury can attenuate both motor and sensory function with minimal potential for full recovery. Research utilizing human induced pluripotent stem cell (hiPSC) -derived spinal cell types for in vivo remodeling and neuromodulation after spinal cord injury has grown substantially in recent years. However, the majority of protocols for the differentiation of spinal neurons are lengthy, lack the appropriate dorsoventral or rostrocaudal specification, and are not typically replicated in more than one cell line. Furthermore, most researchers currently utilize hiPSC-derived motor neurons for cell transplantation after injury, with very little exploration of spinal sensory neuron transplantation. The lack of studies that utilize sensory populations may be due in part to the relative scarcity of dorsal horn differentiation protocols. Building upon our previously published work that demonstrated the rapid establishment of a primitive ectoderm population from hiPSCs, we describe here the production of a diverse population of both ventral spinal and dorsal horn progenitor cells. Our work creates a novel system allowing dorsal and ventral spinal neurons to be differentiated from the same intermediate ectoderm population, making it possible to construct the dorsal and ventral domains of the spinal cord while decreasing variability. This technology can be used in tandem with biomaterials and pharmacology to improve cell transplantation for spinal cord injury, increasing the potential for neuroregeneration.